Model Konseptual Pengaruh Keterlibatan Karyawan terhadap Peningkatan Kinerja Karyawan Generasi Y dan Generasi Z pada Perusahaan Swasta - Foci, Nia Arfina; Amrina, Elita; Hasan, Alizar (Universitas Bunda Mulia, 2024)
Private companies are an industrial sector that greatly contributes to economic development in Indonesia, especially in terms of employment. The lack of employee engagement that dominates the world of work today with different generations is a problem for company leaders in managing their employees. Private companies must have high-performing employees by involving employees to fully contribute to achieving company goals. Evaluation of employee performance needs to be improved by considering aspects of employee involvement. This research aims to design a conceptual model of the influence of employee involvement on private-sector employee performance. Indicators of employee engagement and employee performance were identified from literature studies. Then, indicators were determined that were relevant to private companies in West Sumatra, then sorted the indicators were based on similarity in terminology. The results of the initial identification stage were 52 indicators of employee engagement consisting of indicators in the dimensions of basic need, management support, teamwork, and growth. Employee performance indicators 39 consist of indicators in the dimensions of effort, job knowledge, quantity, quality, compliance with rules, and interpersonal competence. The next step is validation of the indicators by experts from practitioners, academics, and professionals in the field. The validation results state that all indicators are important and relevant for private companies in West Sumatra. This conceptual model is expected to help private companies improve employee performance.